Pengaruh Pemberian Sari Tempe Kurma dan Konseling terhadap Penurunan Kadar Glukosa Darah - Eliza Eliza; Kasturi Kasturi; Muzakkar Muzakkar; Sumarman Sumarman (Jurnal Kesehatan Manarang, 2022)
Diabetes Mellitus was as a chronic disease that happens if the pancreas cannot produce insulin or the body unable to respond to the insulin. A person was diagnosed with Diabetes Mellitus if there were classic symptoms such as polyuria, polydipsia and polyphagia accompanied by high blood sugar levels. The impact of Diabetes Mellitus is a complication of diseases such as heart, kidney, stroke, blindness, and amputation, and one can easily suffer from atherosclerosis. This study was conducted aiming to find out the effect of providing tempe date juice and counselling on blood glucose levels of type 2 Diabetes Mellitus patients in Teluk Kijing Village, Musi Banyuasin Regency. It was a quasi-experimental research with a pretest and posttest design with a control group. The number of respondents in this study was 60 people, determined using purposive sampling. This research showed that most of the majority in the treatment group were aged 40-63 years (90%), female (53%), with elementary school education level (53.3%), and with excess energy intake (56.7%). The average blood glucose level of the respondents in the treatment group before the intervention was 278.8 mg/dl and 222.7 mg/dl after the intervention. The average decrease in blood sugar levels in the treatment group was 56.1 mg/dl. The statistical dependent t-test showed an average difference between blood glucose levels before and after treatment (p= 0.000 < 0.05). The independent t-test showed a significant difference between the treatment results in the treatment group and the comparison group (p= 0.000 < 0.05). It could be concluded that tempe date juice and counselling reduce blood glucose levels in type 2 Diabetes Mellitus patients in Teluk Kijing Village.